Polluting the sea - Hare, Tony. (New York : Gloucester Press, 1991)
Examines the benefits reaped from the oceans and the damage that oil spills, metal poisoning, and sewage dumping cause.
Includes index.
School Library Journal.
6.8
6.8
5-8.
5-8
Keywords: Marine pollution -- Juvenile literature; Marine pollution; Pollution; Marine pollution; Pollution